FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN AKTIVITAS FISIK PENDERITA DM UNTUK PENCEGAHAN KOMPLIKASI DI WILAYAH KERJA PUSKESMAS ROWOSARI KOTA SEMARANG - Astri Zakiyyah; Priyadi Nugraha; Ratih Indraswari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Diabetes mellitus is a disease characterized by increased blood glucose level that exceed normal and metabolic disorders in carbohydrates, proteins and fats due deficiency of the hormone insulin. There are 4 pillars to control diabetes mellitus education; physical activity, regulating diet, and taking medication. The purpose of this study is to find out the factors related to compliance physical activities DM patients to prevent complication in Puskesmas Rowosari. This study is a descriptive analytic study by using design cross sectional research. The sample in this study is DM patients in the Puskesmas work area that were calculated using a sampling technique of 100 people. Data collection was conducted through an interview with the questionnaire. Data analysis was conducted using univariateand bivariate. The result of the research found that there were 59 (59%) respondents are not obedient in physical acitivity. Most of respondents were female (66%), had a primary - secondary education category (93%), had a work category (56%). Most of the respondents were belong in the average age category that was less than equal to 55 years old (57%). The results showed that dependent variable related to age (p = 0.000), gender (p = 0.034), work (p = 0,000), perceived barriers (p = 0.020), self efficacy (p = 0.000), family support (0,000), health worker support (p=0,000). This study concludes that compliance physical activities DM patients most in category disobedient. Therefore, the role of health workers in providing information related to physical activity for patients dm, and provides a facility for do physical activity required ensure that the management of disease DM can be carried out optimally.